2008
DOI: 10.4161/auto.6412
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal injury in rat model of permanent focal cerebral ischemia is associated with activation of autophagic and lysosomal pathways

Abstract: It has been reported that ischemic insult increases the formation of autophagosomes and activates autophagy. However, the role of autophagy in ischemic neuronal damage remains elusive. This study was taken to assess the role of autophagy in ischemic brain damage. Focal cerebral ischemia was introduced by permanent middle cerebral artery occlusion (pMCAO). Activation of autophagy was assessed by morphological and biochemical examinations. To determine the contribution of autophagy/lysosome to ischemic neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
296
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(324 citation statements)
references
References 53 publications
21
296
3
2
Order By: Relevance
“…Electron microscopic analysis has revealed that autophagosomes and autolysosomes are significantly increased in neuronal cytoplasm in the ischemic cortex after pMCAO in rats. Western blot analysis also has shown that the expression of LC3-II and cathepsin B (a main lysosomal protease of the brain parenchyma) are increased in the ischemic cortex [17] . These observations are also supported by Rami et al, who showed that a dramatic elevation in Beclin1 and LC3 levels in the penumbra of rats challenged by tMCAO [15] , and by Puyal et al, who indicated that lysosomal and autophagic activities are increased in the ischemic neurons after transient focal cerebral ischemia [16] .…”
Section: Autophagy Is Activated In Ischemic And/or Hypoxic Damaged Brmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopic analysis has revealed that autophagosomes and autolysosomes are significantly increased in neuronal cytoplasm in the ischemic cortex after pMCAO in rats. Western blot analysis also has shown that the expression of LC3-II and cathepsin B (a main lysosomal protease of the brain parenchyma) are increased in the ischemic cortex [17] . These observations are also supported by Rami et al, who showed that a dramatic elevation in Beclin1 and LC3 levels in the penumbra of rats challenged by tMCAO [15] , and by Puyal et al, who indicated that lysosomal and autophagic activities are increased in the ischemic neurons after transient focal cerebral ischemia [16] .…”
Section: Autophagy Is Activated In Ischemic And/or Hypoxic Damaged Brmentioning
confidence: 99%
“…In addition, autophagy is induced under starvation, differentiation, and normal growth control to maintain homeostasis and survival [1][2][3] ; however, it is also involved in neurodegenerative disorders and can trigger a form of programmed cell death (Type II death) distinct from apoptosis in neurons [4][5][6][7] . Accumulating evidence indicates that autophagy is activated and may be involved in the regulation of neuronal death in different animal models of ischemic brain injury, including hypoxiaischemia (HI) and global and focal ischemia [7][8][9][10][11][12][13][14][15][16][17] . Recently, using a permanent focal cerebral ischemia model of stroke and an oxygen and glucose deprivation (OGD) model in primary cultured astrocytes, the authors show that autophagy is activated in ischemic astrocytes and contributes to astrocytic cell death [18] .…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we found profound activation of autophagy and lysosomes after permanent middle cerebral artery occlusion (pMCAO) and an autophagic mechanism may contribute to ischemic neuronal injury [86] .…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Recent research has shown that ischemic insult activates autophagy, and an autophagic mechanism may contribute to ischemic neuronal injury [11] . Autophagy can be induced by pattern-recognition receptors and stresses such as nutrient depletion, closed head injury, or focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that global ischemia increases the autophagosomes via decreasing autophagosome degradation [16] . The activation of autophagic and lysosomal pathways has been implicated in neuronal injury in a rat model of permanent focal cerebral ischemia [11] . Furthermore, by regulating the TSC2-mTOR-S6K1 signaling pathway, autophagy is induced and further promotes neuronal survival during cerebral ischemia [20] .…”
Section: Introductionmentioning
confidence: 99%